Adoption of food safety measures among Nepalese milk producers: Do smallholders benefit? - Kumar, Anjani; Thapa, Ganesh; Joshi, Pramod Kumar; Roy, Devesh (International Food Policy Research Institute, 2016)
Food safety is the most vital component of food security. One option to ensure food safety is through enhancing compliance at the farm level. This study investigates the status, estimates the cost, identifies the determinants, and assesses the impact of compliance with food safety measures in milk production in Nepal. The study is based on cross-section primary data collected at the farm level from six districts of Nepal. These districts are known for milk production and capture the geographical and institutional diversity of milk production in the country. The study shows that the status of compliance with food safety measures at the dairy farm level is not very encouraging. The intensity with which food safety practices are adopted shows wide inter- and intra-district variations. This intensity depicts a positive relationship to herd size. The additional cost of compliance with food milk safety measures reveals an inverse relationship with herd size. The factors associated with the adoption of food safety measures are caste, number of children and elderly people in a family, household labor size, herd size, access to information, inspection for conformity with the safety and quality standards in dairy farming, perception of households about food safety assistance provided by milk buyers, and market outlet types. We also provide evidence of the impact of food safety measures on farm-gate prices and farmers’ profitability.